Peningkatan Kompetensi Guru PAUD melalui Pelatihan Penulisan Artikel Ilmiah dan Pengembangan Bahan Ajar Berbasis AI - Afdetis Mana, Lira Hayu; Ramadhanti, Dina; Harti, Laspida (Jurnal Gramaswara: Jurnal Pengabdian kepada Masyarakat, 2025)
This training aimed to enhance the professional competence of early childhood and kindergarten (PAUD and TK) teachers in Pariaman City in writing scientific articles and developing teaching materials based on artificial intelligence (AI). Conducted online in a single intensive session, the program combined interactive lectures, participatory discussions, and hands-on practice. A total of 30 participants actively engaged in the training, which focused on the utilization of AI-based applications such as ChatGPT, Grammarly, Mendeley, and Canva. Evaluation was carried out through pre-tests, post-tests, and qualitative observation. The results indicated a significant improvement in participants' understanding of scientific article structure, citation techniques, and creativity in designing interactive teaching materials. The training also succeeded in boosting teachers' motivation to write and publish scholarly works independently. This article underscores the importance of AI technology integration as a transformative strategy for teacher capacity building in the digital era. The novelty of this initiative lies in its practical-empirical approach, combining digital literacy and contemporary pedagogy within the context of early childhood teacher training. Recommendations include the need for ongoing training and personalized mentoring to ensure sustained impact. The outcomes of this program contribute meaningfully to improving teacher quality and accelerating digital literacy in the basic education environment. Keywords: training; scientific paper; preschool and kindergarten teachers